The Class of 1861 : Custer, Ames, and Their Classmates after West Point - Kirshner, Ralph, 1946- (Book collections on Project MUSE., 1999)
"Ralph Kirshner has provided a richly illustrated forum to enable the West Point class of 1861 to write its own autobiography. Through letters, journals, and published accounts, George Armstrong Custer, Adelbert Ames, and their classmates tell in their own words of their Civil War battles and varied careers after the war."--Jacket.